Brain drain, brain circulation, remittances and development : prospects for the Caribbean - Dawson, Laura Ritchie (The Centre for International Governance Innovation WaterlooCA, 2007)
Looks at the issue of brain drain and speculates on the development prospects of brain circulation through return migration. Examines the prospects for economic development through remittances and the engagement of diaspora communities. Concludes that remittances alone are not sufficient for economic development and are, in fact, a reverse subsidy to wealthier countries. Suggests that through domestic reforms and international advocacy and cooperation it may be posible to improve the development returns of highly skilled emigration.